A Free Art Calls for a Free Society: On the Freedom of Art and Autonomy as Project - West, Kim (The Nordic Journal of Aesthetics, 2023)
In recent years, the far right “culture war” has to an increasing extent been allowed to set the terms for cultural policy debates, in Sweden and internationally. In the Swedish context, empty accusations against public cultural institutions of “wokeist” bias and “cancel culture” have found support in a public report from the governmental Agency for Cultural Policy Analysis, which claims that national public funding bodies are imposing politically correct demands on their applicants, with a “detrimental influence” on the freedom of art. This article shows that the ACPA lacks grounds for these claims. Taking its cue from the ACPA’s report, it instead focuses on the fundamental and contested concept of the freedom or the autonomy of art. It seeks to outline what would need to characterise a critical concept of the autonomy of art today, and asks what the political implications would be of a rigorous understanding of such a concept. It argues that cultural policy should be understood as a project of cultural democratization, which should in turn be understood as a project of autonomy.